COMPARATIVE STUDY OF LEAKAGE CURRENT PROPERTIES ON THE NEW-CLEAN PORCELAIN AND EPOXY RESIN OUTDOOR INSULATORS DUE TO VARIOUS PARAMETERS - -, Waluyo; Sinisuka, Ngapuli Irmea; -, Suwarno; Djauhari, Maman Abadurachman (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2010)
This manuscript presents the experimental results of leakage current waveform properties which produced on the new-clean porcelain and epoxy resin insulators due to various voltage, temperature, humidity and pressure parameters. The measurements have been done in the hermetically sealed chamber where the parameters could be regulated and monitored or recorded simultaneously. The examined leakage current parameters were wave amplitude, phase angle or power factor, first to thirteenth odd harmonics and THD. The analysis was done with some multivariate statistical tools, such as correlation matrix, pca and scree plot. The results indicated that leakage current amplitude and phase angle were influenced by humidity, indicated by correlation coefficients as 0.56 and -0.88 respectively on new-clean porcelain insulator. Otherwise, on the new-clean epoxy resin insulator, leakage current magnitude influenced to the phase angle as -0.75. These were supported by principal component analysis. Based on the scree plots, the extracted of information quality were higher than 80%.